Pid-aco vibration controller with magnetorheological damper for wind turbine tower / Mahmudur Rahman - Mahmudur , Rahman (2019)
Vibration in the wind turbine tower disturbs the reliability and increase the possibility of structural damage. Therefore, researchers are very attracted to find suitable solution to minimize vibration in wind turbine tower. Two common vibration control approaches, i.e. passive and active control have the limitations to adapt low frequency, varying loading, and frequency conditions vibrations. It is thus resulted in high external energy consumption in supplying controllable current. Previous studies showed that different controllers for wind turbine vibration control are less effective when the frequency or type of disturbances vary and thus require several tuning processes. In addition, previous research works suggested that it is less effective in vibration reduction when the damper is installed at the top or at the bottom of the tower. Therefore, this research proposes a semi-active vibration control approach for wind turbine tower with optimal tuning of proportional integral derivative (PID) through ant colony optimization (ACO) algorithm and by installing a magnetorheological (MR) damper at the mid-point of the tower to overcome the limitations mentioned above. At first, appropriate dynamic model is estimated using finite difference method (FDM) and system identification process. The FDM dynamic model is found 100% fit to estimated data with reasonably good value of mean squared error (MSE) and Cross Signature Assurance Criterion (CSAC). Next, PID control parameters are optimized with ACO method based on the vibration displacement as objective function to achieve the optimal damping force which is used to encounter vibrations under different excitation frequencies and loading conditions. The placement of MR damper on the tower is then investigated to ensure structural balance and vibration mitigation at all points of the wind turbine tower. It is found that wind turbine tower vibration is reduced up 72% when the damper is placed at middle of the tower and the selection of this optimal location is also based on considerations such as design complexity and maintenance cost. When the proposed optimized PID-ACO controller is tested under different excitations frequencies and loading conditions, results show that the semi-active PID-ACO controller reduces the tower vibration up to 83% and 68% under harmonics excitation at tower 1st mode and random disturbances respectively without the needs of re-tuning the PID parameters. This is effective in preventing structural damage of the wind turbine tower due to unexpected disturbances. This research validates the simulation results with real implementation of lab-scaled wind turbine tower under various loadings such as harmonics excitation at tower 1st mode, sweep frequencies, and random excitations under four damping environments, 1) without damper, 2) passive damper, (i.e. 0 ampere current to MR damper), 3) optimal input current to MR damper, and 4) Locked state, (i.e. high input current to MR damper). It is observed that the real implementation semi-active PID-ACO control system with MR damper reduces up to 73% and 40% of vibration displacement under harmonics excitation at tower 1st mode and random disturbances respectively.